Menilik Historitas Pembaruan Pendidikan Pesantren - Mahfud Ifendi (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
In accordance with the incessant sound of renewal of Islamic thought reformers waged by Muslims from various countries of Egypt, India, Turkey to also echo the update to Indonesia. One of the effects of the